Safety Evaluation Method of Antifloating Anchor System Based on Comprehensive Weighting Method and Gray-Fuzzy Theory. (10th February 2020) - Jingwen, Li; Jiangang, Qiao; Yuanming, Dou; Xu, Fu; Xiaoli, Liu
Abstract : The risk factors in the safety evaluation of antifloating anchor system of underground structure have the characteristics of complexity, grey, and fuzziness. Based on the Delphi method, analytic hierarchy process (AHP), and entropy weight method, this paper establishes a three-level evaluation index system based on four main risk factors and calculates the subjective and objective comprehensive weights of the index according to the comprehensive weighting method. It not only takes into account the valuable experience of the expert group but also reflects the objective impact of the subjective score on the system. On the basis of the above research, the grey-fuzzy safety evaluation method of antifloating anchor system is established by using the grey theory and the relevant theory of fuzzy mathematics. The reliability of the method is verified by an example, which has certain theoretical significance and application value.